Z‐transform for unconditional stable Crank‐Nicolson FDTD implementation of SC‐PML for dispersive Debye media. Issue 25 (1st December 2014) - Li, Jianxiong; Yu, Yang; Zhao, Xiaoming
Abstract : A novel and unsplit‐field implementation of the stretched coordinate perfectly matched layer (SC‐PML) is proposed for truncating the one‐dimensional (1D) frequency dispersive first‐order Debye medium. These formulations are based on the unconditional stable Crank‐Nicolson scheme and the Z‐transform method. Numerical results validate the effectiveness and performance of this new PML.